Weak Equivalence Transformations for a Class of Models in Biomathematics - Igor Leite Freire; Mariano Torrisi (Abstract and Applied Analysis)
A class of reaction-diffusion systems unifying several Aedes aegypti population dynamics models is considered. Equivalence transformations are found. Extensions of the principal Lie algebra are derived for some particular cases.